Agro-morphological characteristics and sensory evaluation of native peruvian chili peppers - Patel, Kirti (2016)
In this work, 31 native Peruvian chili peppers were evaluated for their agro-morphological characteristics and sensory attributes. The descriptive sensory analysis (DSA) was used to evaluate the 31 chili pepper samples based on their acid, bell pepper, sweet, tomato, apple, citrus, fruity, herbal, oregano and passion fruit attributes. The data obtained from the DSA enabled the grouping of these 31 chili peppers into six groups based on their different sensory attributes, such as fruity, bell pepper and herbal. The most abundant group (12 of the 31) had the bell pepper, apple, herbal, fruity and sweet attributes. Each group contained different species and different physical appearances, indicating that species or different forms of chili pepper do not define that sensory attribute. Considering the fact that Peruvian peppers are in high demand, the results achieved would be useful for growers, producers and chefs, as well as for further breeding activities.